Find the value of the polynomial f(y) =6y- 3y2+ 3 at
(i) y = 1 (ii) y = –1 (iii) y = 0
Answers
Answered by
6
Hi pupil here's your answer ::
_____________________________
please see the attached answer
_____________________________
hope that it helps. . . .
_____________________________
please see the attached answer
_____________________________
hope that it helps. . . .
Attachments:
![](https://hi-static.z-dn.net/files/dd3/434d25b63476c37b7dd29da68f92438c.jpg)
Answered by
11
Answer:
(i) 6
(i) -6
(i) 3
Step-by-step explanation:
In the question
(i) y = 1 (given)
Put the value of y in F(y)
= 6 - 3 + 3
= 6 (Answer)
(ii) y = - 1
Put the value of y in F(y)
= - 6 - 3 + 3
= - 6 (Answer)
(iii) y = 0
Put the value of y in F(y)
= 0 - 0 + 3
= 3 (Answer)
Similar questions
Social Sciences,
8 months ago
Social Sciences,
8 months ago
Computer Science,
8 months ago
Chemistry,
1 year ago
Math,
1 year ago